A prevalence study focusing on hospitalized COPD related pulmonary hypertension - Ting-Chia Chang; Ching-Min Wang; Chung-Han Ho; Yi-Chen Chen; Chia-Te Liao; Jiunn-Min Shieh; Wei-Ting Chang (Scientific Reports)
Abstract Pulmonary hypertension (PH) associated with chronic obstructive pulmonary disease (COPD) contributes to mortality. Existing epidemiological research is limited in scale, leading to varied prevalence estimates. Hereby, we aim to evaluate the prevalence and impact of COPD-related PH in individuals with COPD. We used medical-claims data from the national health insurance database (NHIRD) of Taiwan (2009 to 2018). The index date was defined as the initial hospitalization for COPD. We identified patients above 40 year-old with a COPD diagnosis from inpatient claims data and stratified rates of COPD-related PH by gender, age, and COPD severity. We compared short- and long-term mortality between COPD patients with and without PH. To ensure the reliability of our findings, we performed a sensitivity analysis by excluding patients who had not undergone echocardiography. Among 215,292 patients hospitalized primarily for COPD, we found an average COPD-related PH prevalence of 39.9 per 1000 individuals. The annual trend significant declined in prevalence among men but was comparable among women. Furthermore, a higher frequency of COPD-related hospitalization or emergency department visits correlated with an elevated COPD-related PH prevalence, irrespective of age. In comparison to COPD patients without PH, those with this condition exhibited notably higher one-year, three-year, and five-year mortality rates. Collectively, despite a declining trend in COPD-related PH prevalence among COPD patients, its development is closely linked to the severity of COPD. Given the significantly increased mortality rates in COPD patients with PH, early detection of this condition and the implementation of related interventions should be prioritized.